Stereocontrolled synthesis of bicyclic ureas and sulfamides via Pd-catalyzed alkene carboamination reactions - Babij, Nicholas R. (Tetrahedron, 2019)
The synthesis of bicyclic ureas and sulfamides via palladium-catalyzed alkene carboamination reactions between aryl/alkenyl halides/triflates and alkenes bearing pendant cyclic sulfamides and ureas is described. The substrates for these reactions are generated in 3–5 steps from commercially available materials, and products are obtained in good yield with up to >20:1 diastereoselectivity. The stereochemical outcome of the sulfamide alkene addition is consistent with a mechanism involving anti-aminopalladation of the alkene, whereas the stereochemical outcome of the urea alkene addition is consistent with a syn-aminopalladation mechanism.